-2(b+4)+5(5-4b)=-61

Simple and best practice solution for -2(b+4)+5(5-4b)=-61 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(b+4)+5(5-4b)=-61 equation:


Simplifying
-2(b + 4) + 5(5 + -4b) = -61

Reorder the terms:
-2(4 + b) + 5(5 + -4b) = -61
(4 * -2 + b * -2) + 5(5 + -4b) = -61
(-8 + -2b) + 5(5 + -4b) = -61
-8 + -2b + (5 * 5 + -4b * 5) = -61
-8 + -2b + (25 + -20b) = -61

Reorder the terms:
-8 + 25 + -2b + -20b = -61

Combine like terms: -8 + 25 = 17
17 + -2b + -20b = -61

Combine like terms: -2b + -20b = -22b
17 + -22b = -61

Solving
17 + -22b = -61

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-17' to each side of the equation.
17 + -17 + -22b = -61 + -17

Combine like terms: 17 + -17 = 0
0 + -22b = -61 + -17
-22b = -61 + -17

Combine like terms: -61 + -17 = -78
-22b = -78

Divide each side by '-22'.
b = 3.545454545

Simplifying
b = 3.545454545

See similar equations:

| 22=7x+6-3x | | 2n-28=-32+4n | | 3r+5=0 | | 10h-22=48 | | 188.9024=2*3.14*3.2*3.2+2*3.14*3.2*h | | 3(1-5m)-(1+7m)=68 | | 15x+20x=7 | | 41+27= | | 3r-y=0 | | 3.3+10m=7.19 | | 2(x+4)-5(x-3)=18 | | 3=-y+6 | | t*5-4=14 | | 88m^2=3+w | | -6(-3x+6)=90 | | x-2(2x-5)=8 | | 37.50-0.5x=42.75-0.75x | | 15x^2+20x-20=0 | | -109=3-4(8n+4) | | x+82+x+102=180 | | log[2](5x+6)=5 | | 7(t-3)+8t=5(3t+4)-11 | | d+20+0.2d= | | t(x)=11x-725 | | (2x-3)squared=5 | | 5+2x=234234325.00302030303030303030101010324234 | | 2(8n-1)=126 | | 6d+3d+2d-6=3d | | 7v+12b=694 | | X-4x-7=5x(x+21) | | 2(7-2n)=87 | | a*4+8=11 |

Equations solver categories